Halabjah-Iraq Earthquake, Comparisons and General Review - Y. Al-Ghalibi, Furat; Kh. Al-Hadithy, Laith (International Journal of Engineering and Technology, 2018)
The collapsed seismic force level depends on region nature where the construction isÂ to beÂ built because of an earthquake released an energy which generated by a sudden randomly movement of earth segments (plate tectonics). Structure geographic location plays a major role in seismic analysis and design of structures because of the global seismicity influenced by the earthquakeÂ hypocenterÂ and plate tectonics nature. An earthquake will occur if earth tectonic plate shaft and the mass of earth materials moved with plates stress interface and energy released because of ground vibration which its amplitudeÂ reducedÂ with rupture distance. Also the earth vibration generates a large random inertia force thatÂ shouldÂ carried by the structural components safety. In the present study, a comparisons of Halabjah-Iraq Earthquake with many world earthquake is investigated, generally Halabjah earthquake classified as medium risk earthquakeÂ Â